EFEKTIVITAS PELAKSANAAN PERBAIKAN JALAN RUSAK DALAM UNDANG-UNDANG NOMOR 22 TAHUN 2009 TERHADAP KESELAMATAN PENGGUNA JALAN (STUDI PADA DINAS BINA MARGA KOTA BATAM) - Wawan, Wawan; Ukas, Ukas (LPPM Universitas Putera Batam, 2019)
Roads are regional assets enjoyed by the entire community. The government is known to be an institution that has the obligation and authority to maintain and manage roads. But the occurrence of road damage not only results in obstruction of economic activities and other socialization of the community but can cause accidents for road users. In accordance with the Law on Road Traffic and Transportation (LLAJ), Road damage that occurs must immediately get repairs to maintain the safety of road users. Related institutions must provide signs / warning signs to road users so that traffic accidents can be avoided. The research aims at knowing the value of the effectiveness of the implementation rules in the field as well as the causes and solutions in improving damaged road repair services. The method used is an empirical research method, with a qualitative approach. The data obtained are interviews, the results of the study are that the damaged road repair process carried out by the Highways Agency has a system that is considered to require a long time from the planning stage to the execution process in the field, lack of community participation in providing information or reports with various media provided by the government to the community. The conclusion of this study is that the implementation of improvements carried out in the field exists but that the overall improvements carried out are not as effective as in reality based on the rules of the Act. Coupled with a lack of participation and initiative from within the community of road users.